MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2004)
USM EYES BIGGER ROLE IN NATIONAL ROLL-OUT PLAN FOR MSC Universiti Sains Malaysia (USM) is looking to a more prominent role in the impending National Roll-Out plan for the Multimedia Super Corridor (MSC) via its newly-launched satellite earth station in Penang, sources were quoted. USM Vice-Chancellor Professor Datuk Dzulkifli Abdul Razak said yesterday the university’s second 4.5-metre C-band VSAT antenna, which sits atop the School of Computer Sciences’ premises, will enable USM to facilitate more research in areas deemed important in relation to the MSC roll-out. (VSAT technology is a telecommunication system based on wireless satellite technology. The term “VSAT” stands for “Very Small Aperture Terminal”. VSAT technology is made up of a small satellite earth station and a typical antenna of 1.8 metres in diameter). Penang and Kulim have been identified as the new centres of development of the MSC outside Cyberjaya. USM has MSC status, while its corporate arm — Usains Holding Sdn Bhd — has MSC incubator-status. Penang’s MSC Cyber City project will serve as Phase Two of the MSC rollout. Its proposed Cyber City will see the conversion of a portion of the Bayan Lepas Free Industrial Zone on the island linked northwards to USM’s main campus at Minden into the MSC Cyber City. The new antenna found at the satellite earth station is managed by USM’s Network Research Group (NRG) from its School of Computer Sciences. NRG’s Network Head and Programme Chairman Associate Professor Sureswaran Ramadass said since the installation, the antenna has been used extensively for research activities within the Asia Pacific region. The project is led by Keio University of Japan and its partners comprising collaborators and researchers from institutions of higher learning from Asian countries like Thailand, Indonesia and the Philippines.